PERAN DIGITALISASI PEMASARAN PRODUK DALAM MENINGKATKAN PENDAPATAN USAHA TERNAK BURUNG PUYUH PETELUR - Nufus, Hayatun; Yunia, Noorma; Budiman, Budiman; Ilmi Albadiah (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2025)
The development of information and communication technology has brought significant changes to various sectors of life, including the livestock sector. One form of adaptation to these developments is the implementation of digitalization in product marketing activities. This study aims to examine and understand how product marketing digitalization can influence the income of quail farming businesses in Nameng Village. Marketing digitalization refers to the use of various digital media and platforms, such as social media, instant messaging applications, and marketplaces, to market livestock products to consumers more widely and efficiently. This study uses a descriptive qualitative approach, focusing on one quail farming business operator in the Nameng Village area. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation to obtain comprehensive information about the digital marketing practices applied by business operators. This study also considers various supporting and inhibiting factors in the implementation of marketing digitalization, such as access to technology, digital literacy, and the local market's response to digital-based marketing approaches. The results of this study are expected to contribute to the development of more adaptive and relevant marketing strategies for livestock businesses, particularly in the context of utilizing digital technology in today's modern era